TNF‐α antagonism rescues the effect of ageing on stroke: Perspectives for targeting inflamm‐ageing. (2nd June 2021) - Liberale, Luca; Bonetti, Nicole R.; Puspitasari, Yustina M.; Vukolic, Ana; Akhmedov, Alexander; Diaz‐Cañestro, Candela; Keller, Stephan; Montecucco, Fabrizio; Merlini, Mario; Semerano, Aurora; Giacalone, Giacomo; Bacigaluppi, Marco; et al.
Abstract: Aims: Epidemiologic evidence links ischemic stroke to age, yet the mechanisms that underlie the specific and independent effects of age on stroke remain elusive, impeding the development of targeted treatments. This study tested the hypothesis that age directly aggravates stroke outcomes and proposes inflamm‐aging as a mediator and potential therapeutic target. Methods: 3 months‐ (young) and 18‐20 months‐old (old) mice underwent transient middle cerebral artery occlusion (tMCAO) for 30 minutes followed by 48 hours of reperfusion. Old animals received weekly treatment with the TNF‐α neutralizing antibody adalimumab over 4 weeks before tMCAO in a separate set of experiments. Plasma levels of TNF‐ α were assessed in patients with ischemic stroke and correlated with age and outcome. Results: Old mice displayed larger stroke size than young ones with increased neuromotor deficit. Immunohistochemical analysis revealed impairment of the blood‐brain barrier in old mice, i.e. increased post‐stroke degradation of endothelial tight junctions and expression of tight junctions‐digesting and neurotoxic matrix metalloproteinases. At baseline, old animals showed a broad modulation of several circulating inflammatory mediators. TNF‐α displayed the highest increase in old animals and its inhibition restored the volume of stroke, neuromotor performance, and survival rates of old mice to the levels observed in young ones. Patients with ischemic stroke showed increased TNF‐α plasma levels which correlated with worsened short‐term neurological outcome as well as with age. Conclusions: This study identifies TNF‐α as a causative contributor to the deleterious effect of aging on stroke and points to inflamm‐aging as a mechanism of age‐related worsening of stroke outcomes and potential therapeutic target in this context. Thus, this work provides a basis for tailoring novel stroke therapies for the particularly vulnerable elderly population.